Influência das características físico-químicas do esgoto sanitário na desinfecção com ácido peracético - Cavallini, Grasiele Soares; Campos, Sandro Xavier; de Souza, Jeanette Beber; Vidal, Carlos Magno de Sousa (Eclética Química, 2014)
This paper aimed to study the use of peracetic acid (PAA) to disinfect the wastewater. In this perspective, the consume of PAA and its efficiency to deactivate total coliforms microorganisms and E.coli was investigated and under different conditions of total suspended solids (TSS) and pH. The tests of disinfection with PAA demonstrate that content of TSS over than 50 mg/L led to an increase of up to 50% in the consume of disinfectant to the microbial inactivation. The efficiency for inactivation of PAA related to E.coli was also damaged in PH conditions greater than 8. The time of contact had greater influence in the disinfection in dosages up to 5mg/L of PAA.